TRANSMISSION LINE CHANGEOVER SYSTEM FOR LOCAL AREA NETWORK - MURATA TAKESHI (1992)
PURPOSE:To prevent frame out of synchronism to a subordinate node from being caused by making a data delay time in the normal operation equal to a data delay time in the bypass operation. CONSTITUTION:A frame synchronization detection section 3 detecting a frame header representing a delimiter of a frame data gives a timing or the like representing a head of a frame to a transmission line access section 4 and a terminal interface section 6. Moreover, the transmission line access section 4 applies data insertion/branch to a time slot accommodating each terminal equipment and a P/S conversion section 5 converts a parallel data subject to parallel processing into a serial data. Then the terminal interface section 6 applies speed conversion for each data corresponding to the terminal equipment connecting thereto to make transmission and reception of the data to a time slot. Thus, the occurrence of out of frame synchronism of a subordinate mode is avoided.